Differences in iron accumulation in the grain between and within Aegilops and Triticum species - Kastori Rudolf; Maksimović Ivana; Momčilović Vojislava; Mirosavljević Milan; Putnik-Delić Marina; Daničič Milena (Acta Agriculturae Serbica, 2021)
Plants are the most important source of Fe for humans and animals; therefore, its accumulation in edible plant parts is of great importance. Since plant species, ecotypes, genotypes, lines, and varieties may differ in their ability to accumulate mineral elements, the aim of this study was to i) examine the accumulation of Fe in the grain of Aegilops and Triticum species with different genomes (AA, BB, BBAA, BBAADD), ii) study the relationship between the level of ploidy and grain Fe accumulation, and iii) analyze correlations between grain size and Fe concentration. Twenty different genotypes were included in three-year field experiments. The examined species and genotypes differed significantly with respect to grain Fe concentration, which was the highest in diploid Aegilops speltoides (BB genome). Tetraploid and modern cultivated hexaploid varieties displayed substantial variation in Fe concentration in the whole grain. Genotypes also differed significantly in thousand grain weight (TGW), which was the smallest in Aegilops speltoides. A significant negative correlation was found between grain Fe concentration and TGW, and a positive correlation between TGW and Fe content in individual grains. The higher accumulation of Fe in individual grains of tetraploid and hexaploid wheat vs. diploid ancestors suggests that the increase in ploidy led to an increase in the capacity of grains to serve as a sink for that Fe. The results indicate that genetic diversity in the wheat genome is sufficient to allow a significant increase in Fe concentration in the wheat grain.